HUBUNGAN KECEPATAN DAN DAYA LEDAK OTOT TUNGKAI DENGANHASIL LOMPAT JAUH PADA MAHASISWA PUTRA 3B PENJASKESREKANGKATAN 2013 UNIVERSITAS RIAU - Azhari, Rizki Anshari; ', Saripin; Wijayanti, Ni Putu Nita Wijayanti Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT :The results of field observations researchers found problems when students do penjaskesrek son 3B long jump results have not been satisfactory . In order for these skills develop better takes practice and discipline of students in the University of Riau penjaskesrek exercise , in addition to the physical condition is also necessary skills so that mempuni maximum achievable feat . This research is a form of correlation studies with student populations son 3B penjaskesrek 2013 University of Riau forces who took classes 1st semester consists of 33 people . The data in this study is the total sampling technique . The sample is the entire population of the amount , so the sample is 33 people .The instruments used in this research is the speed of a 50 -yard run and test explosive leg muscle power by using the tool Standing broad jump and long jump test . Then the data is processed by stasistic , to test for normality with lilifors test at significance level α = 0.05 , the hypothesis is the relationship of speed and explosive power leg muscles with the results of the long jump .Based on the data processed , it can be inferred correlation of data obtained kooefisien correlation of r r =0,862> rtabel = 0,349  , it can be concluded Ho rejected and Ha accepted , the relationship between the variables X1 and X2 to Y variables significant relationship exists . Conclusion The hypothesis is accepted with a 95% confidence level and a significant level α = 0.05 , thus there is a significant relationship between the speed and explosive power leg muscles with the results of men's long jump 3B penjaskesrek force students 2013 University of Riau . Keywords : Speed ​​and Explosive Power Limbs Muscles , Long Jump Results